The Creating of Singing Book for a Cappella Music Association at Wuhan Technical College of Communication - ChiXiang , Zhang; Danpradit, Pramote (Journal of Roi Kaensarn Academi, 2024)
The purpose of this research is to study the basic singing problems of A Cappella, to create the A Cappella book for students in A Cappella music association of Wuhan Technical College of Communications, to evaluate the results achieved using the A Cappella book.The results were used to create an a cappella singing workbook and tested it by collecting skill assessment scores from 32 A Cappella music association students during and at the end of the term for 16 weeks. The study will be conducted between March 2022 and May 2023. The results of the research are (1) The researchers found the basic singing problems，(2) The researchers summarized and analyzed the results by consulting literature, books and interviewing five experts. Made a new trombone exercise book, including 5 chapters, and formulated a 16-week teaching plan, and (3) The first test result test, the percentage was 80.75, the summative test, the percentage was 92.75, the experimental results showed that the students' professional level improved significantly.